Reversal of Tumor Induced Dendritic Cell Paralysis: A Treatment Regimen Against Cancer - Murugaiyan, Gopal; Basak, Saroj; Saha, Bhaskar (Current Immunology Reviews (Discontinued), 2006)
Dendritic cells (DC) are the most potent antigens presenting cells with the capacity to stimulate naive T cells and induce primary and secondary immune responses. Due to these features DC have been exploited for vaccine delivery in an attempt to actively immunize cancer patients, but the vaccine- induced immune responses have achieved partial success but are not yet sufficient to attain robust and durable therapeutic effect in cancer patients. The partial failure of current vaccine formulations are explained by the extraordinary complexity of the immune response, which makes the task of exploiting the potential of such a therapeutic approach highly challenging. Overall findings obtained from the clinical observations in human suggest that immune system can be polarized against tumor cells by means of DC mediated vaccine. It is clear that there are complex interactions between tumor cells and DC, through their inhibitory effect on DC tumor cells may negatively regulate priming tumor specific immunity. The complete eradication of tumor is possible only when we gain the thorough understanding of DC biology and its interaction with tumor before we design any vaccine formulations using dendritic cells. This review will summarize the recent advances in understanding the role of DC in the regulation of innate and adaptive anti-tumor immunity, and tumor- induced DC paralysis as a major mechanism by which tumors escape host immune response. Knowledge on these aspects will provide important implications for developing more effective DC mediated vaccination against tumor.
Keywords: transforming growth factor-β